ESG, financial distress, firm age, and tax avoidance: evidence from Indonesia and Malaysia - Rahmawati Hanny Yustrianthe; Kumala Jati Eka (Universitas Muhammadiyah Malang, 2026)
Purpose - This study aims to investigate the effect of Environmental, Social, and Governance (ESG) disclosure, financial distress, and firm age on corporate tax avoidance in Indonesia and Malaysia. Design/methodology/approach - Using an unbalanced panel dataset of 435 firm-year observations from publicly listed companies in Indonesia and Malaysia over 2022–2024 period, selected using purposive sampling, and estimates the model using a fixed effects regression with robust standard errors. Tax avoidance is proxied by the Cash Effective Tax Rate (CETR), where lower CETR values indicates a higher level of tax avoidance. Findings - In Indonesia, governance disclosure is associated with higher levels of tax avoidance, while financial distress is associated with lower levels of tax avoidance.. Environmental and social disclosures, as well as firm age do not demonstrate meaningful effects on tax avoidance. In Malaysia, ESG disclosures do not appear to influence tax avoidance. However, financial distress is encourages higher levels of tax avoidance, whereas older firms are less likely to engage in lower levels of tax avoidance. Practical implications - The findings underscore the importance of how institutional and market settings shape the impact of governance and firm attributes on tax strategies, providing key insights for regulators seeking to align corporate sustainability disclosures with fair fiscal contributions in emerging Southeast Asian economies. Originality/value - This study providing empirical comparative evidence on the distinct mechanisms through which corporate characteristics and sustainability disclosures affect tax avoidance across two neighboring emerging markets.